The satisfaction with life scale: psychometric properties in Pakistani population - Barki, Nadia; Choudhry, Riaz Fahad; Munawar, Khadeeja (Iran University of Medical Sciences, 2020)
Background: The construct of satisfaction with life has been studied across various cultures through the Satisfaction with Life Scale. The Satisfaction with Life Scale (SWLS) has been validated across several populations and languages. There are no published psychometric properties of its Urdu version. Hence, the aim of this study was to ascertain the psychometric properties of the Urdu version of the SWLS among the Urdu speaking population of Pakistan. Methods: The SWLS has already been translated into Urdu, and the Urdu version is available on the author’s website however there is no information about its psychometric properties. To establish the psychometric properties especially the factor structure of the already translated Urdu SWLS, the SWLS-Urdu was administered to Urdu speaking population residing in Pakistan. The statistical analyses (i.e., normality through skewness and kurtosis, Kaiser-Meyer-Olkin (KMO) and Bartlett’s test of sphericity, and test and re-test reliability) were conducted through SPSS version 25.0. Structure Equation Modelling via maximum likelihood method of estimation was used to perform confirmatory factor analysis on the data using AMOS 20.0. The significance level was set at p < 0.05. Results: The study was completed by recruiting 120 participants from different universities in Lahore, Pakistan. The sample was equally divided between male and female participants. The mean age of participants was 22.7(3.6) years. Test of the adequacy of the sample through Kaiser-Mayer-Olkin showed KMO=0.88 and Bartlett’s test of sphericity (p<0.001). The Cronbach’s alpha reliability of the scale was 0.90 and Confirmatory Factor Analysis confirmed a one-factor model as a good fit with strong statistical evidence. No factorial group variances were noticed in male and female participants. Conclusion: This study shows that Urdu SWLS has sound psychometric properties, is linguistically and culturally acceptable, and equally useful in assessing satisfaction with life in the Urdu speaking population.